Effect Of Viral Marketing And Brand Awareness On Purchase Intention With Customer Trust As A Mediation Variable in Tik Tok Shop User - Salim, Muhartini; Putri, Seprianti Eka (UNIB Press, 2024)
This research aims to analyze the effect of viral marketing on purchase intention, brand awareness influences purchase intention, customer trust mediates the influence of viral marketing on purchase intention and customer trust mediates the influence of brand awareness on purchase intention. The sampling technique uses purposive sampling. Data was obtained by distributing online questionnaires related to viral marketing, brand awareness, purchase intention, and customer trust to 110 respondents. The sampling technique is purposive sampling and the analysis method is Partial Least Square using the Smart PLS application. The research results show that viral marketing does not affect purchase intention, brand awareness affects purchase intention, customer trust does not mediate the effect of viral marketing on purchase intention and customer trust mediates the effect of brand awareness on purchase intention.